The trapping of microplastics in the Posidonia oceanica aegagropiles in Tunisian coastal areas—Southern Mediterranean - Sghaier, Dhouha Belhaj; Chniti, Ines; Barhoumi-Slimi, Thouraya; Zaaboub, Noureddine; EL Bour, Monia (Frontiers in Marine Science, 2025)
Plastic and microplastic debris (MP) constitute the most important pollutants of the solid litter with a high risk of sediment accumulation. Posidonia oceanica (L.) Delile is the main marine seagrass of the Mediterranean Sea which forms immense underwater meadows and deposits of seagrass beds covering the facades of sandy beaches. They are formed by roots and rhizome fragments gathered in fibrous marine balls, called aegagropiles (EGs), having the ability to trap several pollutants from the beaches and mainly microplastic. The present study aims at evaluating microplastic contamination in aegagropiles collected from four locations along the Tunisian coast in the southern Mediterranean basin (two northern sites (S1 and S2) and two southern-central sites (S3 and S4). Microscopic analysis revealed that red and blue microplastics dominated at all sites, with black fibers and fragments being the most prevalent forms and yellow (S3) and transparent particles in S1, S2, and S4. Polymer identification conducted using nuclear magnetic resonance (NMR) and Fourier-transform infrared spectroscopy (FTIR) detected microplastic types with contamination levels and microplastic accumulation variation among the four sites including polystyrene (PS) at sites S1, S3, and S4; ethyl vinyl acetate (EVA) at S1 and S3; polyethylene terephthalate (PET) at S1 and S2; and polyvinyl chloride (PVC) at S2 and S3. Our results highlight close relationships between anthropogenic activities, extensive plastic use, and elevated microplastic pollution in marine ecosystems, particularly in seagrass beds. These findings emphasize the importance of monitoring microplastic contamination to preserve the health of Mediterranean coastal environments.